MANFAAT IKAN BAGI KESEHATAN (KAJIAN I’JAZ TIBBI QS.AN-NAHL AYAT 14 DALAM KITAB I’JAZ TIBBI FI AL-QUR’AN KARYA DR. SAYYID AL JUMAILI) - Miftakhul Karimah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This study explores the scientific inimitability (i‘jaz tibbi) in the Qur’an concerning the health benefits of fish, focusing on the analysis of Surah An-Nahl verse 14 based on the interpretation of Dr. Sayyid Al-Jumaili. The phrase "lahman tariyyan" (fresh meat) in the verse not only indicates the availability of fish as a source of food but also implies its nutritional and medical value. Employing a qualitative descriptive method through library research, this paper integrates insights from Iʿjaz Tibbi fi al-Qur’an and modern scientific literature in the fields of nutrition and health. The findings reveal that fish is rich in easily digestible animal protein, omega-3 fatty acids, vitamin D, vitamin B12, and essential minerals such as iodine and selenium, which are crucial for maintaining heart, brain, immune system, and thyroid health. This study confirms that the Qur’an provides not only spiritual guidance but also scientific insights relevant to human health, illustrating the harmony between divine revelation and modern science.